Changing hospital culture: the role of an acute palliative care unit. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Paterson, Fiona; Buchanan, Deans; MacIvor, Frances; Lundie, Susan; Levack, Pamela; Baker, Lee
Abstract : Objective: To create a culture in an acute hospital where palliative care is more understood. At a strategic level hospitals accept the need to provide palliative care which is integrated with other hospital activity. It is however, often difficult at ward level to achieve this, especially in addition to 'active' medical treatment. Our advisory palliative care service began in 1998. We now report the benefits of a pilot (2009–10) Acute Palliative Care Unit (APCU) which has now achieved NHS funding. Pilot Acute Palliative Care Unit: Three single rooms in an acute surgical ward 7.6 seconded nurses some with Specialist Palliative Care experience 1.0 Consultant for the APCU and Ninewells advisory service 0.6 Consultant to run an education programme. Admissions: Patients seen by the advisory service with the most complex symptoms or needs. Data: Prospective collection: daily ESAS and distress scores; percentage of patients seeing appropriate disciplines within 2 working days; family meeting; discharge outcome; satisfaction (patient, family and staff). Results: 100 patients were admitted in the first 11 months. Pain was reduced from a median of 7 (IQR 5–10) on admission to 3.5 (IQR 1–5) within 48 h; distress from 7 (IQR 1–10) to 0 (IQR 0–5) within 48 h. There was no significant increase in any symptom (paired t test or Wilcoxon Matched-Pairs Signed Ranks Test). Median length of stay was 5 days (IQR 3–10) and mortality (23%) was low for a palliative care setting. 77% of patients were discharged directly from the unit: 32% home; 26% hospice or community hospital; and 19% to their original ward for active treatment or further consideration of active treatment. Discussion: Seeing specialist palliative care practiced effectively in an acute surgical ward initially intrigued medical and nursing staff but it also encouraged an understanding of each others' disciplines and promoted collaborative working.